Geotechnical Study of Soil Landslides on the 22.7 km Road Section in Quelicai Sub-District, Baucau Regency and Ossu Sub-District, Viqueque Regency, Timor-Leste - Engracia Alves Mendes; Amara Nugrahini (Yayasan Literasi Sains Indonesia, 2026)
The Quelicai–Ossu road section in Timor-Leste, spanning 22.7 km, frequently experiences landslides that disrupt transport connectivity between Baucau and Viqueque districts. These slope failures are exacerbated by steep topography, intense rainfall, and lithological conditions dominated by cohesive clay soils prone to saturation. To address this issue, this study aims to identify and analyse the factors causing landslide vulnerability on the 22.7 km Quelicai–Ossu road section in Timor-Leste. The methods used included field surveys, laboratory testing, and analysis using the Analytical Hierarchy Process (AHP) method combined with GIS. The factors analysed included rainfall, slope gradient, lithology, elevation, drainage, soil type, land use, and road distance. The results of the study show that the study area is divided into three classes of landslide susceptibility: high (19%), moderate (67%), and low (14%). The main factors contributing to landslide susceptibility are rainfall (21%) and drainage (19%). In conclusion, areas with high vulnerability require mitigation measures such as geotechnical engineering to increase slope safety factors to above 1.5. This study provides technical recommendations to reduce landslide risk in the study area.